The degree of employing technology in the school administration in light of the digital transformation From the point of view of a sample of principals of schools in the second cycle in the city of Lattakia - أحمد رنيم; رامي أمون (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The current study aims to measure the degree of employing technology in school administration in light of the digital transformation from the point of view of a sample of principals of the second cycle schools in the city of Lattakia, in the areas of (planning and electronic administrative work - electronic organization - guidance and electronic evaluation - communication with the local community electronically - work on the provision of equipment and infrastructure), a questionnaire consisting of (64) items was built and distributed to (50) female principals of these schools, and we reached the following results: 1- The degree of employing technology in the school administration in light of the digital transformation from the point of view of a sample of principals of the second cycle schools in the city of Lattakia came with a moderate degree of achievement on the questionnaire as a whole, and on the areas of planning, electronic administrative work and infrastructure preparation, and with a large degree on the areas of electronic organization and communication With the local community, and with a weak degree in the field of guidance and electronic evaluation. 2- There is no difference between the averages of the respondents’ responses regarding the degree of employing technology in the school administration in light of the digital transformation according to the variables: educational qualification - years of administrative experience - training courses in the field of computer. 3-There is a difference between the averages of the respondents’ responses regarding the degree of employing technology in the school administration in light of the digital transformation, according to the school dependency variable in favor of private schools.